Epileptic seizures induced by cycloplegic eye drops. (June 2014) - Wygnanski-Jaffe, Tamara; Nucci, Paolo; Goldchmit, Mauro; Mezer, Eedy
Abstract Objective: To assess the incidence of seizures induced by cycloplegic ophthalmic drops. Materials and methods: A survey among members of the American Association for Pediatric Ophthalmology and Strabismus yielded five patients who received cycloplegic eye drops between 1998 and 2010 and who consequently developed a seizure. Results: The median age of the patients was 5 years (range 3 months to 12 years). Cyclopentolate hydrochloride 1% was the only causative agent. The seizure happened on average 12 min after the instillation of dilating eye drops. Three were generalized convulsions, and two patients had a focal seizure. Past medical history was unremarkable in four cases. In total, 16 previous cases of seizures induced by cycloplegic drugs were identified in reports published between 1890 and 2004, implicating atropine in nine reports, tropicamide and phenylephrine eye drops in one and cyclopentolate in six. Discussion: A small amount of cyclopentolate drops could induce convulsions in young children after only minutes to less than an hour, while a larger dosage of atropine over the span of several hours could cause this rare and unpredictable complication. Predisposing factors were rare and those developing the seizures were healthy subjects. Generalized seizures were much more frequent than focal convulsions. Conclusions: Seizures after instillation of cycloplegic drops are extremely rare.